Protagonist participation of older adults and professional performance in Social Work - García Escobar, Jorge (2020)
This text aims to reflect on the protagonist participation of older adults and their close relationship with the professional performance of Social Work. Peru’s demographic reality is constantly changing; a progressive demographic phenomenon is developing: population ageing. At the same time, there are still stereotypes that typecast older adults into a passive person role. Faced with this scenario, they since their protagonist participation, and, through their organizations fighting for their rights, have laid the groundwork for contribute to build an inclusive society, that dignify them as subjects of rights and within the framework of the protagonist paradigm. In the face of this reality, Social Work accompanies values and contributes to the active and decisive participation of this population, making visible their needs, demands and contributions, to fight with them for an inclusive society for all ages; and, realizing his professional performance through public policies.